Advancing a dramaturgical theory of group process. Issue 2 (1st October 2015) - Haen, Craig
This article discusses the application of dramaturgical analysis to understanding process in psychotherapy groups. The author outlines how concepts drawn from the theatre can be used to capture the flow of group process, the roles members take in relationship to one another and the qualities of effective groups. The article suggests how research contributes to building and testing clinical theory, and how a dramaturgical theory of group process may serve both researchers and clinicians.